Penggunaan nitrogen dalam tubuh kambing peranakan etawa yang mendapat bungkil kedelai terproteksi cairan batang pisang - Akhsan, Fitriana; Basri, Basri (Agrokompleks, 2025)
A Protein protection agent in feed components is banana stem liquid. This study aimed to determine the amount of nitrogen (N) utilized by crossbred Etawa goats fed soybean meal preserved with banana stem liquid. The study employed a fully randomized design with three treatments and three replications. Nine crossbred Etawa goats, approximately 5 months old and weighing approximately 7 kg or less, were used in this investigation. The way the treatment is set up. T0 = ​​Basic ration; T1 = T0 + soybean meal with protection from banana stem liquid; 100 grams: 50 cc; T2 = T0 + soybean meal with protection from banana stem liquid. 100 grams: 100 cc. The parameters observed in this study were N consumption, N output (N feces and N urine), N Digest and N Retention. N consumption, N output (N feces and N urine), N Digest, and N Retention.was not affected by different levels of protection (P>0.05). This research concludes that the utilization of nitrogen in the body of Crossbred Etawa goats is not affected by the provision of soybean meal protected by banana stem liquid.